Síndrome de intestino irritable y estrés laboral en docentes de instituciones educativas de la ciudad de Loja - Yanangómez Díaz, María Cristina (2024)
Irritable bowel syndrome (IBS) is part of the functional gastrointestinal disorders, since it is not accompanied by organic alterations or visible lesions, it presents symptoms such as abdominal pain that subsides with defecation associated with changes in deposition, among the factors etiological, there is the psychological one that involves stress as the main cause, so in this research, the main objective was to determine the frequency of Irritable Bowel Syndrome and its relationship with work stress in teachers of Educational Institutions in the city of Loja (San Francisco de Asis , La Porciúncula, Daniel Álvarez Burneo, Santa Mariana de Jesús), for the academic period September 2021-July 2022; Thespecific objectives were to identify the presence of IBS, classify by age and sex, identify the level and sources of work stress and establish the relationship between the level of work stress and IBS in teachers. It was a quantitative, descriptive, prospective and cross- sectional study, in which 161 teachers were sampled and surveys were applied to them for the diagnosis of IBS, levels and sources of work stress, where it was determined that 42.24 % presented IBS, there was a greater predominance in the female sex with 75% in relation to the male sex, the most affected age group was between the range of 20 to 30 years of age, the level of mild stress had a greater predominance with 30 .43%, the source of stress with the highest percentage was the evaluation of work by others. Finally, it was concluded that of the 68 teachers with IBS, the majority presented a medium level of stress, so a relationship was established statistically significant between the presence of work stress and the appearance of IBS